2002
DOI: 10.1021/om010674y
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the Dinuclear Ruthenium Complex {(η5-C5H3)2(SiMe2)2}Ru2(CO)4, Featuring a Doubly Linked Dicyclopentadienyl Ligand

Abstract: The complex {(η 5 -C 5 H 3 ) 2 (SiMe 2 ) 2 }Ru 2 (CO) 4 (1), which features the doubly linked dicyclopentadienyl ligand (η 5 -C 5 H 3 ) 2 (SiMe 2 ) 2 , reacts with phosphines (PMe 3 , PCy 3 , PPh 3 ) to give {(η 5 -C 5 H 3 ) 2 (SiMe 2 ) 2 }Ru 2 (CO)(µ-CO) 2 (PR 3 ) (2a-c), with halogens X 2 (X ) Cl, Br, I) to give the Ru-Ru-cleaved products {(η 5 -C 5 H 3 ) 2 (SiMe 2 ) 2 }Ru 2 (CO) 4 (X) 2 (3a-c), with X 2 and AgTfO to give [{(η 5 -C 5 H 3 ) 2 (SiMe 2 ) 2 }Ru 2 (CO) 4 (µ-X)] + TfO -(X ) Cl, Br, I; 4a-c), and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
2
35
2
Order By: Relevance
“…These molecules deviate from C 2v symmetry only slightly (for complex 2, see the right drawing in Fig. 3), as reflected by their respective minor torsion angle (:Cp(centroid)eRu(1)eRu(2)eCp(centroid): 5.9 for 2; 8.4 for 5; 3.4 for 7; 2.4 for 10), which is much smaller than that (24.2 ) in its analogue (SiMe 2 ) 2 [(h 5 -C 5 H 3 )Ru(CO) 2 ] 2 [13]. The bend of the doubly bridged ligands, defined as the angle between the planes of two Cp rings, is relatively large (131.5 for 2; 130.7 for 5; 131.7 for 7; 130.7 for 10).…”
Section: 2mentioning
confidence: 92%
See 3 more Smart Citations
“…These molecules deviate from C 2v symmetry only slightly (for complex 2, see the right drawing in Fig. 3), as reflected by their respective minor torsion angle (:Cp(centroid)eRu(1)eRu(2)eCp(centroid): 5.9 for 2; 8.4 for 5; 3.4 for 7; 2.4 for 10), which is much smaller than that (24.2 ) in its analogue (SiMe 2 ) 2 [(h 5 -C 5 H 3 )Ru(CO) 2 ] 2 [13]. The bend of the doubly bridged ligands, defined as the angle between the planes of two Cp rings, is relatively large (131.5 for 2; 130.7 for 5; 131.7 for 7; 130.7 for 10).…”
Section: 2mentioning
confidence: 92%
“…The bend of the doubly bridged ligands, defined as the angle between the planes of two Cp rings, is relatively large (131.5 for 2; 130.7 for 5; 131.7 for 7; 130.7 for 10). So nonbonding interactions between highly symmetrical and eclipsed carbonyl ligands and strain resulting from bending the normally planar doubly bridged ligands might be two main factors which lead to significantly greater RueRu bond distances than those in the respective non-bridged and singly bridged biscyclopentadienyl diruthenium analogues ( [5], and even its double-bridged analogue (SiMe 2 ) 2 [(h 5 -C 5 H 3 )Ru(CO) 2 ] 2 (2.8180(3) Å) [13]. This hypothesis is also supported by single crystal X-ray structural data for the series…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…This makes the Ru-Ru and Fe-Fe bond distance [2.7785(11), 2.568 Å ] in 2 and 3 longer than those in the unbridged and many bridged analogues (Table 4). It is reported that the bridging carbonyl groups tend to shorten metal-metal distances [22], and the dicyclopentadienyl dinuclear metal complexes without the bridging carbonyls usually show longer M-M distances that those with the bridging carbonyls. So the Ru-Ru bond distance in 2 is the longest one among the dicyclopentadienyl tetracarbonyl diruthenium complexes with the bridging carbonyls, and even longer than those in (CH 2 ) [(g 5 -C 5 H 4 )Ru(CO) 2 ] 2 [2.766(1) Å ] [23], which has no the bridging carbonyls.…”
Section: Crystal and Molecular Structures Of 2 Andmentioning
confidence: 99%